Pengaruh Pendekatan Konflik Kognitif Terhadap Penurunan Miskonsepsi Peserta Didik Pada Materi Usaha dan Energi - Ita Parwati; Muh. Makhrus; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2019)
This study aims to determine the effect of the cognitive conflict approach to a decrease in studentsÃ¢â¬â¢ misconceptions on business material and energy. This research is a quasi-experimental study with an Ã¢â¬Åuntreatsearch is a quasi-exed control group design withperimental study with pretest and posttestÃ¢â¬Â design. The population in this study were all class X participants of SMAN 1 Gerung with Purposive Sampling sampling techniques.ÃÂ The experimental class (X MIPA 4) was given special treatment in the form of a cognitive conflict approach, while the control class (X MIPA 5) was not given special treatment and continued to study as before. Data on decreasing misconception were measured during learning and based on tests, both data were obtained based on the initial test and final test data. Data, when learning decreases misconception, is obtained based on the percentage decrease in misconceptions that occur. Data to test hypotheses with several variabeles in this study using the IBM SPSS 23 program with a significant 5%. The results of the analysis were obtained ÃÂ so that ÃÂ is rejected and ÃÂ is accepted, so it can be concluded that there is an influence of cognitive conflict approach to a decrease in studentsÃ¢â¬â¢ misconceptions.